Water competence: new insights into swimming and drowning - Langendorfer, S. J. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Langendorfer and Bruya (1995) originally proposed 'water competence' as a gender-inclusive alternative to 'watermanship', to describe aquatic expertise broadly conceived. Other authors (e.g., Stallman, et al. 2008; Moran, et al. 2011) have suggested water competence as minimum performance required to reduce drowning risk. I propose that contemporary science requires envisioning human aquatic performance, learning, and instruction uniquely by associating water competence with five key principles: 1) dynamic; 2) individual; 3) task-related; 4) contextualprobabilistic; and 5) developmental. lt is critical to view water competence dynamically, specifically using Newell's (1986) constraints model, rather than from static 'ability' conceptions. Water competence views efficient and effective control and coordination of aquatic tasks as resultant of interactive relationships among individuals' personal characteristics, specific aquatic environments in which persons find themselves, and unique task demands required. The dynamic developmental view argues against a unitary approach to swimming instruction or to drowning prevention efforts. lt should embrace the notion that individual capabilities emerge in semi-predictable orders across the lifespan as well as moment to moment and from one aquatic situation to the next. Because it recognises the complexity of water competence, I argue for engaging lines of scientific 'strong inference' (Piatt 1964) to explore how persons, aquatic environments, and task demands interact, while searching for the existence of lawful, yet heuristic, principles by which to guide our clinical and professional behaviors in swimming and aquatics.